Model of Campus Mosque Development in Promoting Religious Moderation: A Cross-Case Study of Five Universities in West Java - Aid Samsudin; Momod Abdul Somad; Syihabuddin; Edi Suresman (UIN Sunan Gunung Djati Bandung, 2026)
Religious moderation is an increasingly pressing national priority in Indonesia. However, campus mosque programs, despite their strategic position as co-curricular development spaces in higher education, have not been systematically designed based on measurable moderation indicators. This study aims to: describe the operational model of campus mosque revitalization in promoting religious moderation among students; and assess the strengths and weaknesses of this model in relation to the objectives of religious moderation. A qualitative cross-sectional case study was conducted at five purposively selected campus mosques in West Java: Al-Furqon Mosque (UPI), Salman Mosque (ITB), Ikomah Mosque (UIN Sunan Gunung Djati), Agung Mosque (UNPAD), and Ukhuwah Islamiyah Mosque (UI). Data were collected through in-depth interviews, focus group discussions, contextual observations, and document analysis, then analyzed using thematic analysis. The revitalization of campus mosques in the five locations was implemented through three integrated dimensions of worship, education, and welfare with a cadre-based and inclusive management system. Its main strengths are: holistic development, inclusive governance, cadre sustainability, and contextual responsiveness. However, weaknesses remain: the lack of indicator-based design, standard operating procedures, monitoring and evaluation mechanisms, minimal interfaith literacy, and formal integration with general and character education. In conclusion, campus mosques have a strong foundation for religious moderation, but require a more structured, indicator-based, and institutionalized revitalization model to ensure measurable and sustainable impact.